Time to talk? Patient experiences of waiting for clinical management of knee injuries. Issue 2 (2nd April 2009) - Robling, M R; Pill, R M; Hood, K; Butler, C C
Abstract : Background: People with knee problems face long waits for elective surgery in many parts of the world. However, there is little evidence about the impact of delays in such treatment, especially for patients with mechanical knee injuries. Objective: To conduct a detailed exploration of patient experiences of waits for specialist diagnosis and surgery for knee injuries at one UK centre. Research design: In-depth qualitative paired interviews with a range of patients at baseline and 6 months later. Subjects: Patients awaiting imminent therapeutic arthroscopy of the knee (n = 20) or recently referred from primary care for specialist opinion or imaging for a knee injury (n = 19). Sample stratified to maximise variation by gender and age. Results: 36 patients completed both interviews. Four topic areas were identified. First, problems in the healthcare system were highlighted, including a lack of adequate information, which made it difficult for patients to make decisions about their lives. Second, patients experienced a social and psychological cost of waiting. Third, patients varied in their ability to cope and demonstrated both passive and proactive coping strategies. Fourth, patients described the management effectiveness of clinicians and their ability or otherwise to provide support. Conclusions: A detailed qualitative approach has identified broad physical and psycho-social consequences for patients with knee injuries experiencing delays in clinical management. An overarching theme was the important potential of both systemic and interpersonal communication to improve patient well-being. A managed care pathway which enhanced information provision may provide immediate opportunities for improving patient well-being.